Diffraction Efficiencies of Three Types of Bioplastic Gratings Based on Chitosan from Seafood Waste - Gumayan, Efren G. (Archīum Ateneo, 2023)
We report an initiative on promoting sustainability in optical manufacturing by repurposing waste materials as bioplastic diffractive elements. Bioplastic diffraction gratings are fabricated from three chitosan solutions via soft lithography. Chitosan is prepared from seafood waste in the form of powdered crab shells through demineralization, deproteination, depigmentation, and deacetylation. For soft lithography of chitosan gratings, a mold is constructed from a polydimethylsiloxane (PDMS) grating replica of a commercial master grating with groove density of 600 lines/mm. The three chitosan solutions are each poured into the PDMS mold and allowed to harden. Once fully cured, the chitosan replicas are carefully extracted from the mold. We perform diffraction experiments at normal incidence with an Ar+ laser operating at 514.5 nm and 25 mW. Measured first-order power efficiency of the unmodified chitosan grating is 0.7%. The bioplastic gratings made from chitosan-starch and chitosan-glycerol both exhibit a first-order diffraction efficiency of 0.5%. These values are comparable with the 0.9% first-order efficiency of the PDMS replica used in the molding process.